The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1007/s002239900651
|View full text |Cite
|
Sign up to set email alerts
|

Early Postmenopausal Bone Loss is Prevented by Estrogen and Partially by 1α-OH-vitamin D3: Therapeutic Effects of Estrogen and/or 1α-OH-vitamin D3

Abstract: A total of 79 Japanese women who were within 5 years of menopause were randomly assigned 1alpha-hydroxyvitamin D3 [1alpha(OH)D3] 1.0 microg/day, conjugated estrogens 0.625 mg/day, a combination of both, or control (no treatment). Lumbar spine and proximal femur bone mineral density (BMD) and biochemical indices were monitored over 2 years. In the 1alpha(OH)D3-treated group, there was a nonsignificant decrease in lumbar spine BMD compared with controls, and no significant loss in the femoral neck compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Similar results were reported from a study in Japanese women within 5 years after menopause 26 . Thus, the change in BMD demonstrated in this study is of similar magnitude to existing published data, although the studies are not directly comparable.…”
Section: Monotherapy Combinationsupporting
confidence: 90%
“…Similar results were reported from a study in Japanese women within 5 years after menopause 26 . Thus, the change in BMD demonstrated in this study is of similar magnitude to existing published data, although the studies are not directly comparable.…”
Section: Monotherapy Combinationsupporting
confidence: 90%
“…Some investigators have already examined the combination therapy of estrogens for HRT and ALF. Gorai et al [26] found a synergistic effect of HRT and ALF on early postmenopausal bone loss to be only marginal. In addition, neither Gallagher et al [27] nor Komulainen et al [28] could find any further beneficial effects on bone loss in the combination therapy of HRT and ALF compared with those in HRT alone.…”
Section: Discussionmentioning
confidence: 99%
“…We have already reported that a synergistic bone-sparing effect can be expected when estrogen is administered concomitantly with alfacalcidol [1a-hydroxyvitamin D 3 ] rather than when used alone in postmenopausal Japanese women with osteopenia, suggesting that vitamin D status is not sufficient in early postmenopausal Japanese women [16]. However, in the previous study, serum levels of 25(OH)D were not measured when the subjects were enrolled in the clinical trial [17].…”
Section: Introductionmentioning
confidence: 90%